If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4u + -5)(3 + u) = 0 Reorder the terms: (-5 + 4u)(3 + u) = 0 Multiply (-5 + 4u) * (3 + u) (-5(3 + u) + 4u * (3 + u)) = 0 ((3 * -5 + u * -5) + 4u * (3 + u)) = 0 ((-15 + -5u) + 4u * (3 + u)) = 0 (-15 + -5u + (3 * 4u + u * 4u)) = 0 (-15 + -5u + (12u + 4u2)) = 0 Combine like terms: -5u + 12u = 7u (-15 + 7u + 4u2) = 0 Solving -15 + 7u + 4u2 = 0 Solving for variable 'u'. Factor a trinomial. (-3 + -1u)(5 + -4u) = 0Subproblem 1
Set the factor '(-3 + -1u)' equal to zero and attempt to solve: Simplifying -3 + -1u = 0 Solving -3 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1u = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1u = 0 + 3 -1u = 0 + 3 Combine like terms: 0 + 3 = 3 -1u = 3 Divide each side by '-1'. u = -3 Simplifying u = -3Subproblem 2
Set the factor '(5 + -4u)' equal to zero and attempt to solve: Simplifying 5 + -4u = 0 Solving 5 + -4u = 0 Move all terms containing u to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -4u = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -4u = 0 + -5 -4u = 0 + -5 Combine like terms: 0 + -5 = -5 -4u = -5 Divide each side by '-4'. u = 1.25 Simplifying u = 1.25Solution
u = {-3, 1.25}
| 6b^2+23=11 | | 40/4=5x+2(-4x) | | 5/4(x+2)=3 | | 5w+41=3(w+9) | | 0.333333(x+3)+0.1666666(x-6)=x+3 | | (4x+1500)-(2x+1800)=0 | | -4/3x^2-19/18x-19/36=0 | | 2y+3=3(7+7) | | G+2(3+g)=4(g+1) | | 2=400/x | | (x+5y)dy=-(2x+3y)dx | | 7=5(x+5)-7x | | onethird(x+3)+onesixth(x-6)=x+3 | | 5xa-7a^2=2a^2+2ax | | -6x-3(7x-26)=-111 | | 4a-2a+11=6a-13 | | 9w+5= | | 5ax-7a^2=2a^2+2ax | | 8(-7+8v)=200 | | 9w-5= | | 1p-15=13-6p | | 10p+6=-18-2p | | 29=4x-5 | | 2x^2=-2 | | -9v-6+7v=16 | | (2x+1500)-(4x-1800)=0 | | 5x-13=11+3x | | -18-[3(x+2)+4]=21-[6(-2x-2)+1] | | (x+5y)dy+(2x+3y)dx=0 | | -(5/12)y=25 | | 16+3s-2s=24+2s | | xxxx=69 |